2004
DOI: 10.1124/dmd.104.002253
|View full text |Cite
|
Sign up to set email alerts
|

tert-BUTYLHYDROQUINONE IS A NOVEL ARYL HYDROCARBON RECEPTOR LIGAND

Abstract: ABSTRACT:In contrast to the beneficial effects of tert-butylhydroquinone (tBHQ) as a food antioxidant, a number of studies have shown that chronic exposure to tBHQ may induce carcinogenicity. Therefore, we examined the ability of tBHQ to induce the cytochrome P450 1a1 (Cyp1a1), an enzyme known to play an important role in the chemical activation of xenobiotics to carcinogenic derivatives. A significant concentration-dependent increase in Cyp1a1 mRNA, protein, and activity occurred after treatment of murine hep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
1
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 83 publications
(61 citation statements)
references
References 34 publications
5
49
1
2
Order By: Relevance
“…Combined TCDD/tBHQ treatment of HepG2 cells led to a decrease in all the parameters measured (DRE reporter activity, CYP1A1 mRNA expression, and CYP1A activity) when compared with values obtained with TCDD alone. tBHQ has been shown to bind and activate the AhR (Gharavi and El-Kadi, 2005). However, it may behave as a partial agonist that, when present at a very high concen- tration compared with TCDD, may lower the maximal achievable inducing effect of the latter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Combined TCDD/tBHQ treatment of HepG2 cells led to a decrease in all the parameters measured (DRE reporter activity, CYP1A1 mRNA expression, and CYP1A activity) when compared with values obtained with TCDD alone. tBHQ has been shown to bind and activate the AhR (Gharavi and El-Kadi, 2005). However, it may behave as a partial agonist that, when present at a very high concen- tration compared with TCDD, may lower the maximal achievable inducing effect of the latter.…”
Section: Discussionmentioning
confidence: 99%
“…This study was initiated because we had previously observed that phenolic antioxidants can induce human UDPglucuronosyltransferase 1A6 by a mechanism in which DRE binding of the AhR plays some role (Münzel et al, 2003). Moreover, two recent studies report on an inducing effect of tBHQ on CYP1A1 in HepG2 cells (Sugatani et al, 2004) and Hepa1c1c7 cells (Gharavi and El-Kadi, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…To determine the protein expression pattern of the main P450 epoxygenases, CYP2Bs, CYP2C11, CYP2C23, and CYP2J3, and the main P450 hydroxylases, CYP4As, and CYP4Fs for each organ, Western blot analysis was performed using a previously described method (26). Briefly, 5-40 μg of heart, lung, kidney, and liver microsomal preparations were separated by 10% sodium dodecyl sulfate-polyacrylamide gel (SDS-PAGE), and then electrophoretically transferred to nitrocellulose membrane.…”
Section: Western Blot Analysismentioning
confidence: 99%
“…Accordingly, none of these antioxidants can be used in food for infants and children. Prolonged exposure to very high doses of TBHQ may also be carcinogenic (Gharavi and Kadi, 2005). However, the European Food Safety Agency (EFSA) reported that TBHQ is a safe food additive if only authorized doses are applied to foodstuff (Scientific Opinion, 2004Race, 2009).…”
Section: Bha Bht and Tbhqmentioning
confidence: 99%